Boswellic Acid Synergizes With Low-Level Ionizing Radiation to Modulate Bisphenol Induced-Lung Toxicity in Rats by Inhibiting JNK/ERK/c-Fos Pathway - Somya Z. Mansour; Fatma S. M. Moawed; Monda M. M. Badawy; Hebatallah E. Mohamed (Dose-Response, 2020)
Bisphenol A (BPA) is a low molecular weight chemical compound that has a deleterious effect on the endocrine system. It was used in plastics manufacturing with injurious effects on different body systems. Occupational exposure to low-level ionizing radiation (<1 Gy) is shown to attenuate an established inflammatory process and therefore enhance cell protection. Therefore, the objective of this study was to investigate the protective effect of boswellic acid (BA) accompanied by whole-body low-dose gamma radiation (γ-R) against BPA-induced lung toxicity in male albino rats. BPA intoxication induced with 500 mg/kg BW. Rats received 50 mg BA/kg BW by gastric gavage concomitant with 0.5 Gy γ-R over 4 weeks. The immunoblotting and biochemical results revealed that BA and/or γ-R inhibited BPA-induced lung toxicity by reducing oxidative damage biomolecules; (MDA and NADPH oxidase gene expression), inflammatory indices (MPO, TNF-α, IL-6, and gene expression of CXCR-4). Moreover, BA and or/γ-R ameliorated the lung inflammation via regulation of the JNK/ERK/c-Fos and Nrf2/ HO-1 signaling pathways. Interestingly, our data demonstrated that BA in synergistic interaction with γ-R is efficacious control against BPA-induced lung injury via anti-oxidant mediated anti-inflammatory activities.